Plasma and synovial fluid as solvents for monosodium urate. Issue 1 (February 1981) - Dorner, R W; Weiss, T D; Baldassare, A R; Moore, T L; Zuckner, J
Abstract : In-vitro differences in monosodium urate (MSU) crystal dissolution in paired plasma and synovial fluid samples from patients with various arthritides were studied. Plasma was a significantly better solvent for MSU than synovial fluid (overall difference 6.3 mg/dl (0.37 mmol/l); significant at P less than 0.001). Attempts to correlate the solubility differentials with the principal compositional differences between the 2 fluids were only partially successful. (1) A tendency towards higher MSU solubility at higher protein levels was observed, but it was too slight to reach statistical significance. (2) Hyaluronidase treatment of synovial fluid significantly enhanced its ability to dissolve MSU (overall difference 2.2 mg/dl (0.13 mmol/l); significant at P less than 0.01) but not sufficiently to explain wholly the plasma-synovial fluid differential.